Medicamentos à base de canabidiol para o tratamento de epilepsia: uso terapêutico e regulamentação brasileira - Silva, Emily Lorrany Guedes da (Brasil, 2024)
The Cannabis sativa species, popularly known as marijuana, has 60 cannabinoids. The most studied is Cannabidiol (CBD), due to its anticonvulsant properties and, especially, the absence of psychotomimetic effects and risk of developing dependence, typical of Δ-9-tetrahydrocannabinol (THC). In view of this, cannabinoid derivatives are gaining ground in the treatment of epilepsy, a disease characterized by being a chronic neurological disease, generally progressive, generating cognitive alterations according to the frequency and severity of critical events, called seizures. In view of the above, this study aimed to conduct a bibliographic survey on the therapeutic use of Cannabidiol-based medications in the treatment of epilepsy and the Brazilian regulation of these medications. A search was carried out in the databases: Google Scholar, Pubmed and BDTD, for articles published from 2014 -2024, using the keywords: Cannabidiol, Epilepsy, Therapeutic use and Brazilian Regulation. Twenty-eight articles were selected after the analyses, it was concluded that the use of Cannabidiol is effective for the treatment of epilepsy, on the other hand, the regulation, although it is already allowed for medicinal purposes in Brazil, still brings many clashes and discussions, requiring public policies focused on the subject so that access to these medicines is released more easily within the regulatory standards.